2020
DOI: 10.1186/s13568-020-01130-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microflora related to growth performance in pigs based on 16S rRNA sequence analyses

Abstract: Intestinal microorganisms have been shown to be important factors affecting the growth performance of pigs. Therefore, to investigate the effect of the intestinal microflora structure on the growth performance of pigs, samples from Duroc (n = 10), Landrace (n = 9) and Yorkshire (n = 21) pigs under the same diet and feeding conditions were collected. The fecal microbial composition was profiled via 16S ribosomal RNA (rRNA) gene sequencing. We also analyzed their growth performance. We found that Duroc and Landr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The population structure of gut microbiota in vertebrates is regulated by both environmental and genetic factors of the host (Zhao et al, 2013). Previous studies have shown that there were significant differences in intestinal microbial composition among different breeds of pigs (Yang et al, 2014;Li et al, 2020). In our study, PCoA and ANOSIM analysis clearly showed distinct population structure at species level among four pig breeds, which confirmed the differences of intestinal microbes among different pig breeds.…”
Section: Discussionsupporting
confidence: 85%
“…The population structure of gut microbiota in vertebrates is regulated by both environmental and genetic factors of the host (Zhao et al, 2013). Previous studies have shown that there were significant differences in intestinal microbial composition among different breeds of pigs (Yang et al, 2014;Li et al, 2020). In our study, PCoA and ANOSIM analysis clearly showed distinct population structure at species level among four pig breeds, which confirmed the differences of intestinal microbes among different pig breeds.…”
Section: Discussionsupporting
confidence: 85%
“…Of interest, in our findings, the genus Lactobacillus was the second leading bacterium in the jejunum. Li et al (2020) also found that Lactobacillus consisted in the gut of healthy pigs. Lactobacillus had a strong antibacterial activity, which enhanced the health of the chickens by inhibiting the growth of pathogens through competitive exclusion in the gastrointestinal tract ( Ahmed et al, 2019 ).…”
Section: Discussionmentioning
confidence: 88%
“…Reduced numbers of Ruminococcus can be associated with diarrhea in suckling piglets therefore, this genus also may have association with animal body weight. The resent study also detected significant relation between Barnesiella and Lactobacillus to the growth performance in Yorkshire pigs ( 44 ). Lactobacillus also induces porcine host defense peptides and therefore improving immunity ( 45 ).…”
Section: Resultsmentioning
confidence: 83%